Modeling Crowded Environment in Molecular Simulations - Ostrowska, Natalia; Feig, Michael; Trylska, Joanna (Frontiers in Molecular Biosciences, 2019)
Biomolecules perform their various functions in living cells, namely in an environment that is crowded by many macromolecules. Thus, simulating the dynamics and interactions of biomolecules should take into account not only water and ions but also other binding partners, metabolites, lipids and macromolecules found in cells. In the last decade, research on how to model macromolecular crowders around proteins in order to simulate their dynamics in models of cellular environments has gained a lot of attention. In this mini-review we focus on the models of crowding agents that have been used in computer modelling studies of proteins and peptides, especially via molecular dynamics simulations.